PERUBAHAN KEBIJAKAN DALAM SISTEM PENEMPATAN DAN PERLINDUNGAN PEKERJA MIGRAN INDONESIA STUDI KASUS: PENEMPATAN SATU PINTU PMI KE ARAB SAUDI TAHUN 2022 - ', Selfia; Retnaningsih, Umi Oktyari (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
Indonesian migrant labors benefit Indonesian society economically and socially for remmitance and unemployment solution. The evidence showed they do not receive ample protections and services from Indonesian government locally and internationally. Indonesian government has launched a new policy for the system of placement and protection of migrant workers to Saudi Arabia. The study elaborated the new policy implementations and the results for Indonesian migran labors advantages. This research is qualitative research. Secondary data collection came from analyzing documents of books, journals, official reports, and news from newspapers. Interviews with former Indonesian migrant unskilled labors were done to complete and triangulate data from secondary sources. A constructivist perspective with the theory of diplomatic protection where every country is obliged to protect its citizens was utilized. This research showed changes in policies regarding the placement and protection of migrant workers benefited them. The one-stop migrant worker placement system could help maximize the provision of protection to migrant workers. Several programs such as the Desa Migran and the KUR loan scheme by the government could help prospective migrant workers. Fortunately, the program is still ongoing to protect migrant workers and their families for the better lives. Keywords: BP2MI, Government, Indonesian Migrant Workers